Top bunk, bottom bunk: cellsharing in prisons - Schliehe, Anna K. (The British journal of criminology, 2022)
The politics involved in cell-sharing reach into the most personal parts of prisoners’ lives and are highly determinate of their experiences of imprisonment. While there is a small amount of research on the impact of cell-sharing on personal wellbeing and prison quality, much less has been written about the daily dynamics and significance of negotiating shared space under conditions of coercion. In this paper, based on in-depth research undertaken in England & Wales, we explore the experience of cell-sharing and how dynamics in the cell matter both intimately and socially. Essentially, we locate the cell as one of the primary sites of ‘where the action is’ in prisons, and where matters of safety, dignity and abjection are of particular relevance.